A movable technological simulation system for kinematic analysis to provide immediate accurate feedback and predict javelin throw distance - Essam Eldin Hassan (Selcuk University, 2015)
The use of information technology (IT) and highly sophisticated devices in learning and evaluating training process is very common in today's sport sciences. The research aimed is a Trying to identify using of the biomechanical simulation system to evaluate physical variables in javelin throw. A new movable biomechanical simulation system to expect the javelin throwing distance and evaluate physical variables was developed, which consisted of a 800g sledge to be accelerated along a rope. The release angle can be adjusted within the range of 26 - 40 degrees. The takeoff height can be likewise adapted to the individual conditions of the athlete. By a laser-steered measure (LAVEG) the velocity of the throw carriage can be determined. 20 sport students were selected. The research proves that only 10 seconds are needed to show the expected distance. This research also recommends using this new movable technological biomechanical simulation system in learning and evaluating training processes.